Reproductive biology of Rhodophiala bifi da (Amaryllidaceae): applica- tion aspects in breeding. (FAVE Sección Ciencias Agrarias, 2021)
Rhodophiala biﬁda is a bulbous species native to Argentina, Brazil, Paraguay and Uruguay. The size and color of its ﬂowers make it very attractive for ornamental cultivation. The development of domestication and breeding protocols are essential to propose it as a new crop, considering that the global ﬂoricultural industry requires novelties. As a starting point, compatibility and reproductive efﬁciency studies were carried out through controlled crosses considering phenotypes of ﬂowers of different color. Both self-pollination and cross-pollination produced fruits, so a mixed reproductive system was veriﬁ ed in R. biﬁda. Reproductive efﬁciency was signiﬁcantly higher in cross-pollination than in self-pollination, being 49.6 and 19 respectively, for red ﬂowers, the most representative genotype of the population. No fruiting was observed in emasculated ﬂowers without pollination, so autonomous apomixis was ruled out. The crossings among phenotypes produced fruits except for the case of crossings between pink by fuchsias ﬂowered phenotypes.
Keywords: selfcompatibility; reproductive efficiency; plants native to Argentina; ornamentals; breeding.